2020
DOI: 10.1186/s12879-020-4831-4
|View full text |Cite
|
Sign up to set email alerts
|

STI in times of PrEP: high prevalence of chlamydia, gonorrhea, and mycoplasma at different anatomic sites in men who have sex with men in Germany

Abstract: Background: Men who have sex with men (MSM) are disproportionally affected by sexually transmitted infections (STI). STI are often extragenital and asymptomatic. Both can delay diagnosis and treatment. Approval of HIV preexposure prophylaxis (PrEP) might have influenced sexual behaviour and STI-prevalence of HIV-MSM. We estimated STI-prevalence and risk factors amongst HIV-and HIV+ MSM in Germany to plan effective interventions. Methods: We conducted a nationwide, cross-sectional study between February and Jul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
75
4
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(106 citation statements)
references
References 63 publications
20
75
4
7
Order By: Relevance
“…Regardless of the question, the best STI knowledge was identified among PrEP-users. In our population, this group was exclusively constituted by MSM and, in line with other cohorts, reported a significantly higher number of sexual partners, exposure to chemsex and history of STIs, as well as less frequent condom use [8]. STI awareness in the MSM population has been evaluated in recent studies, although with contradictory results, depending on the study population and the STI being evaluated (consistently better for HIV than for other STIs) [9,10].…”
Section: Discussionsupporting
confidence: 71%
“…Regardless of the question, the best STI knowledge was identified among PrEP-users. In our population, this group was exclusively constituted by MSM and, in line with other cohorts, reported a significantly higher number of sexual partners, exposure to chemsex and history of STIs, as well as less frequent condom use [8]. STI awareness in the MSM population has been evaluated in recent studies, although with contradictory results, depending on the study population and the STI being evaluated (consistently better for HIV than for other STIs) [9,10].…”
Section: Discussionsupporting
confidence: 71%
“…The prevalence of HIV among MSMs in the present study was 5.36%; among 575 MSMs from the Netherlands, it was 3.5%; 4 among 2303 MSMs from Germany, 50.5% 5 and in Colombia, a study with 336 MSMs from Bucaramanga reported 11% prevalence. 18 Despite the differences in HIV occurrence, all studies report very high prevalence in this population, thus corroborating the need to join efforts to screen MSMs for infection.…”
Section: Discussioncontrasting
confidence: 53%
“…Studies with MSMs have reported prevalence of 3.5% and 50.5%, with risk factors as high number of sexual partners, sex without condoms, drug use and other STIs. [4][5][6] Among sex workers, the prevalence has been 5% -70%, with a high co-infection of syphilis (5%), chlamydia (8%) and gonorrhoea (2%). 7,8 In persons deprived of liberty have been reported prevalence as low as 0.47% or 2-10 times higher than the general population.…”
Section: Introductionmentioning
confidence: 99%
“…A lack of association between condom use and STI increments was found in one Australian cohort, maybe due to other unknown or unmeasured risk behaviours such as an increase in having new sexual partners [ 21 ]. Nevertheless, the relation between having an STI and PrEP use has been controversial: while some studies have found that PrEP use would increase STI incidence [ 22 24 ], others show that PrEP would not lead to STI increases or would even lower STI rates, due to frequent testing and close follow-up of sexual health [ 25 ]. This would be consistent with the fact that having STIs and not using condoms consistently in the last 12 months were inclusion criteria for the study, as well as being and indicative criteria in the national guidelines.…”
Section: Discussionmentioning
confidence: 99%